Implementation of Learning Management In Building an Attitude of Religious Tolerance at State High Schools In The Muna District - La Hadisi; Miftahur Rahman Hakim; Zulkifli Musthan; Husna Nashihin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aimed to describe and reveal a portrait of student diversity and management of PAI learning in building an attitude of religious moderation in public high schools in the Muna District. This Research used a qualitative approach, and data were collected through interviews, observations, and documents. From this study it can be seen that the results of the study show: (1) the portrait of diversity in SMA Negeri Muna Regency is: (a) SMAN 1 Raha has 1125 Muslim students, 10 Christians and 2 Hindus (b) SMA Negeri 2 Raha students who 1256 Muslims are Muslims and the number of students who are Christians is 38 people; (c) SMA Negeri 1 Tongkuno has 490 Muslim students and 18 Christian Catholic students (d) SMA 1 Tongkuno Selatan has 93 Muslim students and 29 Christian Catholics; (2) The implementation of PAI learning management in building Tolerance at public high schools in Muna Regency is as follows: (a) The planning for PAI learning in fostering Tolerance has been established in the national education system; (b) Implementation which includes intra-curricular activities, extra-curricular activities or additional classes, and routine activities and habituation of cooperation and (c) The evaluation phase is carried out through an assessment of the completeness of each basic competency in each material taught as well as attitude and spiritual assessment sheets in observing students' daily behavior.